PROBLEMATIKA PILKADA LANGSUNG; STUDI KASUS PELAKSANAAN PILKADA LANGSUNG DI PROVINSI SUMATERA UTARA 2005-2007 - Yusa' Farchan; Partono Partono (Jurnal Renaissance, 2016)
The local elections directly that has been held since 2005 is a long process of struggle democracy in Indonesia. This research analyze about the local elections directly in some districts in the province of north Sumatra in the period 2005-2007. This research employe in a qualitative approach field research. Technique the data collection was conducted through focus group discussion (FGD), in-depth the interview, questionnaire and media review. The results research indicate that the election directly during 2005- 2007 in the north Sumatera is still dyed with several crucial problems, such as, Voter registration; candidacy, the existence of desk election; campaign; neutrality of the election stakeholders; neutrality supervision committee (Panwas); participation and voters behaviour; the preparation of moment and the funds of the local election; the role and the behavior of political party behavior; demonstrations and media violence. To intensify the quality of election, improvements to systems absolutely necessary, as complete mechanism voter registration; to intensify the participation of voters; political education voters; and strengthening the skill, the competence and integrity of the local election.Key words: evaluation the local elections, the local elections in the North Sumatra